Teoria da modernidade e razão comunicativa em Habermas - Anjos Júnior, José dos (2015)
The present paper is dedicated to Habermas’s theory of modernity, in particular as regards to the concepts of racionalization, reification and reason communicative. These concepts are devoloped from the Habermas’s critical reflection in dialogue with Max Weber and Georg Lukacs, considering these strongly constituted the link between theory of modernity and social theory. Reason whereby, to pursue the proposed aims, it will examined, especially the work “The theory of communicative action” (1981). Indeed, the Habermas’s theory of modernity, when face with Weber and Lukács, constitutes the research object this investigation, whose problem can be formulated as follows: how the Habermas’s theory of modernity provides the basis of his concept of communicative racionality? Weber understands the pathologies of modernity as “loss of meaning” and “loss of freedom, both resulting from the process of “social racionalization”. Lukács, in his appropriation and transformation of Weber, elaborates such pathologies under the concept of “reification”. Habermas, in turn, puts the problem in terms of “colonization of the life world” by social system. As Habermas attributes to both character unilateral analysis of time, by take in account only a narrow concept of rationality, he seeks to develop a diagnosis that encompasses the pathologies of the modernity in all its amplitude, offering like anwer the concept of communicative rationality. Thus, his theory of the modernity provides the diagnostic time, identifying the pathologies of modernity, whose therapy is task indicated to communicative racionality.